Exposición al Dicloro Difenil Tricloroetano y perfil tiroideo durante el embarazo: revisión sistemática y meta-análisis - Hernández-Mariano, José Ángel; Castañeda-Márquez, Ana Cristina; Fragoso, Lucero Analy; Orbe-Orihuela, Yaneth Citlalli (Horizonte Sanitario, 2023)
Objective: Evaluate the association between p,p´-DDT and p,p´-DDE exposure with thyroid disruption during pregnancy through meta-analysis. Material and methods: We performed a systematic review and meta-analysis based on the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA).  The protocol of this review was registered in PROSPERO with the identification sheet: CRD42022324797. We conduct systematic searches in PubMed and Web of Science electronic databases to identify eligible studies published in English and Spanish up to January 2, 2022. Using random-effects meta-analysis, a beta regression coefficient was estimated (β) pooled, for each hormone of the thyroid profile, from the β published in each study and their 95% confidence intervals (95% CI).Results: Eight studies were included, of which only three reported biomarkers of exposure to p,p'-DDT, so it was not possible to conduct a meta-analysis to assess the relationship between this compound and hormones in the thyroid profile. Exposure to p,p'-DDE was associated with a slight increase in TSH (pooled β= 0.05; 95% CI= -0.01, 0.12) and total T3 (pooled β= 0.02; 95% CI= -0.05, 0.09) levels , but inversely with total T4 (β pooled= -0.003; 95% CI= -0.05, 0.05) and free T4 (β pooled= -0.01; 95% CI= -0.03, 0.01) levels, although neither of these findings was statistically significant.Conclusions: The evidence available to date is still limited to draw a conclusion on the association between the variables of interest. Since small changes in thyroid homeostasis in pregnant women could have consequences on fetal development, it is necessary to continue generating evidence in this regard.Keyword: Dichloro-diphenyl-trichloroethane; Dichloro-diphenyl-dichloroethylene; thyroid hormones; pregnancy.